Abasener und Adulis - Müller, Walter W. (Aethiopica, 2008)
The publication of the first volume of a new critical edition of the Ethnica of Stephanos of Byzantium gives occasion to enumerate the eleven toponyms on the Ethiopian side of the Erythraean Sea which are mentioned in this geographical lexicon. Furthermore an attempt is made to localize the Abasenoi, a tribe in Arabia, which are identical with the Ḥabašat, taking in account the agricultural products of their country. Concerning the harbour of Adulis, which is the origin of the ʿadawlī-ships in early Arabic poetry, further testimonies of this town in literary sources are adduced and a plausible South-Arabian etymology of the name Adulis is proposed.